Enhancing Tourism Promotion in Arjasa Village: Towards Global Recognition as a Traditional Tourism Village - Dzulkifli, Muhammad; Milawaty, Milawaty; Rizka, Hablana; Nasir, Fuad; Qastalano, Rezha Isyraqi; Harliansyah, Amelia; Kamal, Mushthofa; Agustianto, Khafidurrohman (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
Arjasa Traditional Tourism Village is a rural tourism destination located in Jember Regency. Its primary target market currently consists of local tourists, particularly those interested in history, traditional customs, and cultural heritage. Although the village has attracted some international visitors, their numbers remain limited. To enhance global recognition and increase the number of foreign tourists—both annually and during specific cultural events—there is a need for the development of strategic tourism promotion initiatives. Hence, the main objective of this research is to examine the development of tourism promotion strategies in Arjasa Traditional Village. This research used a qualitative- descriptive approach, with data collection techniques including direct observation, in-depth interviews, and literature review. The research results encompass the creation of attractive tour packages, robust promotional programs, and the establishment of broader networks across the ASEAN region. The findings are expected to contribute to the formulation of a comprehensive tourism promotion plan that can be implemented by the village's tourism management to improve visibility and visitor engagement.